Stimulation of Resistance of Immunocompromised Mice by a Muramyl Dipeptide Analog - Osada, Yasuaki (1982)
L18-MDP(Ala), a synthetic derivative of muramyl dipeptide, enhanced resistance against Escherichia coli and Candida albicans infections in aged mice and younger adult mice whose defense mechanism(s) had been depressed by X-ray irradiation or by treatment with cyclophosphamide.